2003
DOI: 10.1107/s0108768103004634
|View full text |Cite
|
Sign up to set email alerts
|

Structure of lithium benzilate hemihydrate solved by simulated annealing and difference Fourier synthesis from powder data

Abstract: The crystal structure of lithium benzilate hemihydrate (C(14)H(11)O(3)(-)Li(+).0.5H(2)O) was solved from synchrotron powder diffraction data. This compound crystallizes in the monoclinic space group P2(1)/a. The structure was solved via the direct space search for two benzilate fragments using the simulated-annealing program DASH, localization of the lithium ions and water molecule from a difference Fourier map, and a restrained Rietveld refinement (R(wp) = 0.0687). The structure is a coordination polymer of [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The orientations of the phenyl rings in the benzilate moieties are those of propeller blades, as found in lithium benzilate 13 , potassium benzilate 14 , and the various benzilate derivatives found in the CSD Database 37 . This conformation minimizes the repulsive interactions between the geminal phenyl rings.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The orientations of the phenyl rings in the benzilate moieties are those of propeller blades, as found in lithium benzilate 13 , potassium benzilate 14 , and the various benzilate derivatives found in the CSD Database 37 . This conformation minimizes the repulsive interactions between the geminal phenyl rings.…”
Section: Resultsmentioning
confidence: 88%
“…In continuation of our previous investigation on coordination polymers 13,14,[24][25][26][27] , in this work, we present the synthesis, structural characterization and energetic properties of the new coordination polymer strontium benzilate. Hirshfeld surface analysis 28 was used for visually analyzing intermolecular interactions in the crystal structure.…”
Section: Introductionmentioning
confidence: 93%
“…In the structural investigations of benzilate complexes, it has been found that the benzilic acid functions as a multidentate ligand with versatile binding and coordination modes (Mora et al, 2003;Rojas et al, 2003). In this paper, we report the structure of the title compound, a copper(II) complex obtained by the reaction of benzilic acid, 1,10-phenanthroline (phen) and copper chloride in an alkaline aqueous solution.…”
Section: Methodsmentioning
confidence: 99%